Investigation of the photocatalytic potential enhancement of silica monolith decorated tin oxide nanoparticles through experimental and theoretical studies. (27th July 2020) - Khan, Idrees; Khan, Adnan Ali; Khan, Ibrahim; Usman, Muhammad; Sadiq, Muhammad; Ali, Faiz; Saeed, Khalid
Abstract : Photodegradation of organic pollutants is considered to be the most suitable and cheaper technique to counter decontamination issues. Abstract : Photodegradation of organic pollutants is considered to be the most suitable and cheaper technique to counter decontamination issues. Metal nanoparticles are considered the most effective heterogeneous photocatalysts for photodegradation of organic pollutants, but neat nanoparticles agglomerate in the reaction medium and display less photocatalytic efficiency. Herein, silica monolith particles (SiO2 ) were synthesized and utilized as a support medium for the synthesis of SnO2 nanoparticles to retard their agglomeration. Silica-supported tin oxide nanoparticles (SnO2 /SiO2 NPs) and neat tin oxide nanoparticles (SnO2 NPs) were prepared through chemical reduction method and characterized by AFM, SEM, TEM, EDX and mapping, XRD, FTIR and zeta sizer. Morphological and mapping analyses revealed that SiO2 increases the surface area of SnO2 NPs and magnificently enhances their photocatalytic activity. The neat SnO2 NPs are highly agglomerated and hence show less photocatalytic activity. XRD and FTIR analyses confirm the synthesis of SnO2 NPs. The neat SnO2 NPs have a PDI of 0.51, which reveal much variation in the particles' size and have a surface charge of −11.2 ± 0.87 mV, which is not enough for the NPs' repulsion in suspended form and hence are agglomerated. The SnO2 /SiO2 NPs degraded about 94.58% and 93.73% orange II (O II) dye while SnO2 NPs degraded 65.93% and 46.11% dye within 30 min irradiation under UV and visible light respectively. The enhanced photocatalytic activity of SnO2 /SiO2 NPs is due to the synergistic effect of rapid adsorption followed by drastic photodegradation of dye. The SnO2 /SiO2 NPs are much more sustainable than SnO2 NPs due to easy recycling and washing and the recovered SnO2 /SiO2 NPs degraded about 83.38% of dye while SnO2 degraded 21.91% within 30 min. In addition, the density functional theory (DFT) calculations show that the SnO2 /SiO2 NPs have greater adsorption capacity then pristine SiO2 and SnO2 surfaces, having shorter binding distances, a larger E ads value (4.29 eV) and a larger reduction in band gap.